Effect of Metal Corrosion on the Maximum Deflection of I-Section Steel Beams subjected to Sudden Short-Duration Constant Force - Nguyen, Duy Duan; Nguyen, Trong Ha (Engineering, Technology & Applied Science Research, 2025)
This paper aims to determine the effect of metal corrosion on the maximum deflection of I-section steel beams subjected to sudden constant force in a short duration. To calculate this type of deflection, a model was developed and subsequently combined with a metal corrosion model, considering the beam’s cross-section and stiffness reduction. A series of investigations of the maximum steel beam deflection in different corrosive environments were carried out. The results showed that the maximum deflection of I-section steel beams varied from 6.63% (in rural environments) to 29.62% (in marine environments) after 100 years. These findings highlight the importance of considering long-term corrosion effects when designing steel structures, particularly those exposed to sudden and sustained forces in a short time.